Prolactin, a potential biomarker for chronic GVHD activity. (26th October 2020) - Salas, Maria Queralt; Ezzat, Shereen; Lam, Wilson; Law, Arjun Datt; Pasic, Ivan; Michelis, Fotios V.; Kim, Dennis Dong Hwan; Gerbitz, Armin; Al‐Shaibani, Zeyad; Viswabandya, Auro; Kumar, Rajat; Mattsson, Jonas; et al.
Abstract: Introduction: The polypeptide prolactin (PRL) is a peptide hormone and a cytokine mostly secreted from the anterior pituitary gland. PRL is also synthesized in extra pituitary tissues including thymocytes and T lymphocytes. Considering the need for chronic GVHD (cGVHD) biomarkers, we explored the relationship between hyperprolactinemia and active cGVHD in a cohort of long‐term post‐alloHCT survivors. Methods: Three‐hundred sixteen adults underwent alloHCT between 2010 and 2016, survived more than 1 year and were included. All patients underwent a regular annual assessment that includes a hormone profile with serum PRL levels. Results: Overall, 236 (74.7%) patients had cGVHD, and in 199 (63%), the grade was moderate or severe. Sixty‐five (21%) recipients had active cGVHD at the time of the annual evaluation, and hyperprolactinemia was documented in 63 (19.9%) patients. Hyperprolactinemia correlated with cGVHD activity (Odds Ratio 6.9 (95% CI; 3.6‐13.1); P < .001) in the multivariate analysis. In conclusion, patients with hyperprolactinemia were 6.4 times more likely to have active cGVHD in comparison with those patients with normal levels of PRL ( P < .001). Conclusion: Prolactin may serve as a biomarker for cGVHD activity. Further studies are required to confirm these findings, and to explore if hyperprolactinemia has an impact on cGVHD severity and prognosis.